Use of Social Media and Consumer Behavior towards Students Lifestyle in Lampung - Pegi Pradana; Rian Pangestu; Lisa Ayu Fitriani; Vicki F Sanjaya (JURNAL MUTIARA MANAJEMEN, 2020)
Social media is a group of internet-based applications built on the ideology and technological foundations of web 2.0 which enable the creation and exchange of generated content. Consumer behavior is the study of how individuals, groups, and organizations select, buy, use, and position goods, services, ideas, or experiences to satisfy their needs and wants. The development of student consumer behavior is influenced by their family origin, environment, psychology, culture, and lifestyle. Lifestyle is a pattern in which people spend time and money. Nowadays, lifestyle is very influential on student behavior. Now, social media has become a necessity for everyone, especially for students, it has become their primary need. The use of social media can affect the student's lifestyle, but it may also not affect the student's lifestyle. This study is to determine the use of social media and consumer behavior towards student lifestyle. This type of research is a quantitative research based on the results of several samples using a questionnaire containing related statements. Data were collected using a questionnaire and processed using partial least squares. The results showed that social media and consumer behavior towards lifestyle had a positive effect on students